Hospitalization for partial nephrectomy was not associated with intrathecal opioid analgesia: Retrospective analysis - Toby N Weingarten; Serena B Del Mundo; Tze Yeng Yeoh; Federica Scavonetto; Bradley C Leibovich; Juraj Sprung (Saudi Journal of Anaesthesia, 2014)
Background: The aim of this retrospective study is to test the hypothesis that the use of spinal analgesia shortens the length of hospital stay after partial nephrectomy. Materials and Methods: We reviewed all patients undergoing partial nephrectomy for malignancy through flank incision between January 1, 2008, and June 30, 2011. We excluded patients who underwent tumor thrombectomy, used sustained-release opioids, or had general anesthesia supplemented by epidural analgesia. Patients were grouped into "spinal" (intrathecal opioid injection for postoperative analgesia) versus "general anesthetic" group, and "early" discharge group (within 3 postoperative days) versus "late" group. Association between demographics, patient physical status, anesthetic techniques, and surgical complexity and hospital stay were analyzed using multivariable logistic regression analysis. Results: Of 380 patients, 158 (41.6%) were discharged "early" and 151 (39.7%) were "spinal" cases. Both spinal and early discharge groups had better postoperative pain control and used less postoperative systemic opioids. Spinal analgesia was associated with early hospital discharge, odds ratio 1.52, (95% confidence interval 1.00-2.30), P = 0.05, but in adjusted analysis was no longer associated with early discharge, 1.16 (0.73-1.86), P = 0.52. Early discharge was associated with calendar year, with more recent years being associated with early discharge. Conclusion: Spinal analgesia combined with general anesthesia was associated with improved postoperative pain control during the 1 st postoperative day, but not with shorter hospital stay following partial nephrectomy. Therefore, unaccounted practice changes that occurred during more recent times affected hospital stay.